2015
DOI: 10.1134/s0006297915040021
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role of alternative oxidase (from yeasts to plants)

Abstract: Mitochondria of all so far studied organisms, with the exception of Archaea, mammals, some yeasts, and protists, contain, along with the classical phosphorylating cytochrome pathway, a so-called cyanide-insensitive alternative oxidase (AOX) localized on the matrix side of the mitochondrial inner membrane, and electron transport through which is not coupled with ATP synthesis and energy accumulation. Mechanisms underlying plentiful functions of AOX in organisms at various levels of organization ranging from yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 96 publications
1
30
0
Order By: Relevance
“…This report improves our understanding of the protective role played by Aox in plants, fungi and some protozoa against the most diverse experimental stresses [2526]. …”
Section: Discussionmentioning
confidence: 77%
“…This report improves our understanding of the protective role played by Aox in plants, fungi and some protozoa against the most diverse experimental stresses [2526]. …”
Section: Discussionmentioning
confidence: 77%
“…Mitochondria of most organisms studied so far contain, along with the classical phosphorylating cytochrome pathway, a so‐called cyanide‐insensitive alternative oxidase (AOX), localized on the matrix side of the mitochondrial inner membrane (Rogov and Zvyagilskaya, ). It has been demonstrated that Aspergillus fumigatus produces an AOX that contributes to both reductions of ROS generated within mitochondria and regulation of energy production and metabolism (Hattori et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…An alternative oxidase system is found in all plants, most fungi, algae, and some protists (Rogov and Zvyagilskaya, 2015). Aox is located in the inner mitochondrial membrane where it receives electrons from reduced ubiquinone and catalyzes the reduction of oxygen to water.…”
Section: Introductionmentioning
confidence: 99%